Analysis of Digital Marketing Strategies through GoFood in Enhancing Community Purchasing Power at Cafe Raluna Paiton Probolinggo - Ririn Filda Yanti Ningsih; Fahrudin (Darul Yasin Al Sys, 2026)
The rapid development of digital technology has encouraged culinary businesses to adopt online food delivery platforms, particularly GoFood, to expand market reach and improve customer service. However, the effectiveness of such platforms depends on operational capacity and alignment with local consumer preferences regarding price, convenience, and practicality. This study analyzed the implementation of digital marketing strategies through GoFood in improving community purchasing power at Cafe Raluna, Paiton District, Probolinggo Regency. A qualitative descriptive design was employed. Data were collected through observation, in-depth interviews, and documentation involving four informants: the manager, cashier, and an employee of Cafe Raluna, as well as a consumer who had previously ordered through GoFood. The data were analyzed using an interactive model comprising data reduction, data display, and conclusion drawing. The findings indicate that Cafe Raluna’s use of GoFood incorporates the four elements of the marketing mix—product, price, place, and promotion. Nevertheless, the promotional features and menu presentation have not been managed through systematic planning, thereby limiting digital marketing performance. GoFood contributes to increased community purchasing activity by providing convenient services, practical ordering processes, and promotional programs that encourage purchases. However, the magnitude of this contribution could not be determined because GoFood sales were not recorded separately from direct sales. Additional constraints included limited driver availability, platform commission fees, and competition among culinary businesses. The study concludes that GoFood supports Cafe Raluna’s digital marketing and community purchasing power, although more systematic planning, separate sales recording, and optimized promotional and menu-management strategies are required to achieve sustainable outcomes. These findings provide practical implications for small culinary businesses seeking to improve the effectiveness of platform-based digital marketing.